The partnership with parents to special needs middle and high school (Journal of Parents and Teachers, 2013)
This article is a reflection of the role that the school and the families should have in relation to the students and their educational special needs during Secondary Education and Higher Secondary Education. When we talk about this kind of students, the Spanish education system supports the principles of inclusion and normality. However, the daily practice shows that the diversity tends to be perceived, understood and attended from excepcionality. This position risks the actions that were created to attend these type of students. An effective help in terms of respect requires specific trainning of the teacher body, the incorporation of parents into schoolar support and leadership of the school in the procces. In any case, the departments of schoolar orientation should plung the coordination of all thesee actions.
Keywords: Pedagogic orientation; parents-students relation; teacher-student relation; individual characteristic; Personality